Hypertension Is Associated With Intestinal Microbiota Dysbiosis and Inflammation in a Brazilian Population - Silveira-Nunes, Gabriela; Durso, Danielle Fernandes; Jr., Luiz Roberto Alves de Oliveira; Cunha, Eloisa Helena Medeiros; Maioli, Tatiani Uceli; Vieira, Angélica Thomaz; Speziali, Elaine; Corrêa-Oliveira, Rodrigo; Martins-Filho, Olindo Assis; Teixeira-Carvalho, Andrea; Franceschi, Claudio; Rampelli, Simone; et al. (Frontiers in Pharmacology, 2020)
Hypertension is a major global health challenge, as it represents the main risk factor for stroke and cardiovascular disease. It is a multifactorial clinical condition characterized by high and sustained levels of blood pressure, likely resulting from a complex interplay of endogenous and environmental factors. The gut microbiota has been strongly supposed to be involved but its role in hypertension is still poorly understood. In an attempt to fill this gap, here we characterized the microbial composition of fecal samples from 48 hypertensive and 32 normotensive Brazilian individuals by next-generation sequencing of the 16S rRNA gene. In addition, the cytokine production of peripheral blood samples was investigated to build an immunological profile of these individuals. We identified a dysbiosis of the intestinal microbiota in hypertensive subjects, featured by reduced biodiversity and distinct bacterial signatures compared with the normotensive counterpart. Along with a reduction in Bacteroidetes members, hypertensive individuals were indeed mainly characterized by increased proportions of Lactobacillus and Akkermansia while decreased relative abundances of well-known butyrate-producing commensals, including Roseburia and Faecalibacterium within the Lachnospiraceae and Ruminococcaceae families. We also observed an inflamed immune profile in hypertensive individuals with an increase in TNF/IFN-γ ratio, and in TNF and IL-6 production when compared to normotensive ones. Our work provides the first evidence of association of hypertension with altered gut microbiota and inflammation in a Brazilian population. While lending support to the existence of potential microbial signatures of hypertension, likely to be robust to age and geography, our findings point to largely neglected bacteria as potential contributors to intestinal homeostasis loss and emphasize the high vulnerability of hypertensive individuals to inflammation-related disorders.